Anthelmintic efficacy of mebendazole and levamisole in Olive Baboon (Papio anubis) infected with Trichuris trichiura. - Sohail Afzal; Uzma Farid Durrani; Asim Khalid Mahmood; Amber Fatima; Raheela Akhtar; Abdul Mateen; Amira S H Hassenin (PLoS ONE, 2025)
The olive baboon (Papio anubis) belongs to the family Cercopithecoidea and lives in different environmental conditions as well as they are also kept in zoological gardens as a source of public entertainment. Poor growth and health disorders are commonly reported issues in olive baboons in captivity mainly because of gastrointestinal infections and endo-parasites. The present study was conducted on 15 dewormed olive baboons kept in Lahore Zoo, Lahore, Pakistan, and diagnosed with Trichuris trichiura (roundworm). Infected olive baboons were selected and randomly divided into 3 groups, i.e., A, B, and C. Group A and B were treated with mebendazole (20 mg/ kg, PO) and levamisole (10 mg/kg, PO), respectively. Group C was designated as a non-treated control group. Direct smear technique and simple fecal floatation technique were performed to diagnose positive samples. Pre- and post-treatment fecal screening was performed on days 0, 7, 14, 21, and 28. The effect of both anthelmintics on EPG values was calculated by pre- and post-treatment fecal screening. Egg per gram (EPG) was determined by using the McMaster technique. EPG values were used to determine the fecal egg count reduction (FECR). Statistically, there was a significant decrease in EPG values from days 0-14. On day 28 EPG values were significantly lower than day 0. There was a significant statistical difference between the treated and control groups P < 0.05, but there was no statistically significant difference between the mebendazole group and levamisole-treated groups (P > 0.05). Based on the numerical difference of mean EPG values and comparison between mebendazole and levamisole group; mebendazole was less effective than levamisole in olive baboons against Trichuris species. Repeated treatment was suggested for complete clearance of worm infestation in both treated groups.